2016
DOI: 10.1159/000448583
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Schwannoma Resection with Ipsilateral Simultaneous Cochlear Implantation in Patients with Normal Contralateral Hearing

Abstract: Objective: To report the hearing results of cochlear implantation simultaneous to vestibular schwannoma (VS) resection by means of a translabyrinthine approach in patients with normal contralateral hearing. Methods: This was a prospective study including adults with sporadic VS. Tumors were resected by means of a modified translabyrinthine approach with preservation of the cochlear nerve. Results: A total of 13 patients underwent cochlear implantation. At 14 months, the mean pure-tone audiogram was 56 dB. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 34 publications
(39 reference statements)
4
48
0
1
Order By: Relevance
“…Similar to Rooth et al, the prospective study by Sanna et al also showed a significant improvement in sound localization as well as subjective improvement in hearing outcomes in daily situations. 16 Taken together, these studies indicate that while open-set recognition is an important measure to consider when evaluating the efficacy of this intervention, additional outcome measures such as localization and quality of life should need to be considered.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Similar to Rooth et al, the prospective study by Sanna et al also showed a significant improvement in sound localization as well as subjective improvement in hearing outcomes in daily situations. 16 Taken together, these studies indicate that while open-set recognition is an important measure to consider when evaluating the efficacy of this intervention, additional outcome measures such as localization and quality of life should need to be considered.…”
Section: Discussionmentioning
confidence: 97%
“…Postoperative magnetic resonance imagings (MRIs) are routinely performed for tumor surveillance after surgery. 16,30 The receiver-stimulator and magnet distort radiographic images obtained after CI. Some considerations raised in included studies include altering placement of internal hardware to avoid distortion and avoidance of CI if there is a reasonable suspicion for residual tumor or possibility of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in the introduction, the benefits to CI placement in single-sided deafness are well established. 14,15 Sanna et al 27 prospectively evaluated CI placement simultaneous with translabyrinthine tumor resection with intact contralateral hearing with good results. The data gathered from this study was insufficient to evaluate the effect of an intact contralateral ear on CI outcomes with VS. As long as there is sufficient cochlear nerve function for a CI to function normally, it is reasonable to expect similar outcomes in these patients as others with singlesided deafness.…”
Section: Discussionmentioning
confidence: 99%